Characteristics and outcomes in community‐acquired versus hospital‐acquired acute kidney injury. Issue 3 (25th February 2013) - Schissler, Michael M; Zaidi, Syed; Kumar, Haresh; Deo, Datinder; Brier, Michael E; McLeish, Kenneth R.
Abstract Aim Relatively little is known about the prevalence of acute kidney injury developing outside a hospital setting (CA‐AKI) or the impact of CA‐AKI on short‐term or long‐term clinical outcomes. The objective of this study was to compare the prevalence, causes, severity and outcomes of patients with CA‐AKI and hospital‐acquired (HA)‐AKI. Methods A retrospective cohort study of patients with AKI identified by ICD‐9 code at a single VA (Veterans Affairs) hospital from September 1999 to May 2007 was performed. AKI was verified by applying the RIFLE criteria, and patients were categorized as CA‐AKI if RIFLE criteria were met at admission. Demographic, clinical, and outcome variables were extracted by chart review. Results Four hundred twenty‐two patients met inclusion criteria, of which 335 (79.4%) developed CA‐AKI. Patients with CA‐AKI were more likely to have volume depletion as the aetiology, had fewer chronic illnesses and hospital complications, had a shorter length of stay, and had a reduced mortality, compared with HA‐AKI. Distribution among the three RIFLE classes did not differ between groups, and recovery of renal function was incomplete in both groups. Conclusion We conclude that CA‐AKI is a common cause of AKI that is as severe as that seen in HA‐AKI. CA‐AKI has a significant impact on length of hospital stay, mortality, and the development and/or progression of chronic kidney disease. Strategies to limit the risk of CA‐AKI are likely to have a significant impact on healthcare costs and patient care.